2018
DOI: 10.1016/j.ajme.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Rolling up the pieces of a puzzle: A systematic review and meta-analysis of the prevalence of toxoplasmosis in Iran

Abstract: a b s t r a c tToxoplasmosis is a neglected parasitic disease with global distribution in warm-blooded vertebrates and high prevalence among different human societies. We contrived a systematic review and meta-analysis on the prevalence of toxoplasmosis in Iran. Following the general methodology recommended for systematic reviews and meta-analysis, four English and three Persian electronic databases were explored up to April 2016. Out of 105,139 examined samples of different hosts, the weighted overall prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…It has been well demonstrated that suppression of the host immune response is an important risk factor for the reactivation of chronic infections. Other important risk factors for T. gondii infection are intake of sporulated oocysts from contaminated water or unwashed fruit and vegetables, keeping cats indoors as pets, and the consumption of raw or undercooked meat containing T. gondii tissue cysts [ 1 , 4 , 10 , 12 ]. The geographical area is also an important factor associated with the prevalence of T. gondii infection [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well demonstrated that suppression of the host immune response is an important risk factor for the reactivation of chronic infections. Other important risk factors for T. gondii infection are intake of sporulated oocysts from contaminated water or unwashed fruit and vegetables, keeping cats indoors as pets, and the consumption of raw or undercooked meat containing T. gondii tissue cysts [ 1 , 4 , 10 , 12 ]. The geographical area is also an important factor associated with the prevalence of T. gondii infection [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasmosis is a cosmopolitan parasitic zoonosis caused by the well-known intracellular protist, Toxoplasma gondii [ 1 , 2 ]. Recently published systematic review articles have estimated the pooled prevalence of global T. gondii infection in various groups of humans.…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasma gondii belongs to the Apicomplexa phylum that caused a widespread zoonotic infection in a wide range of intermediate hosts, including men, livestock, birds, marine mammals, and snakes [ 1 2 3 4 5 6 7 ]. More than one century ago, this protist was discovered from the spleen and liver smears of a north African rodent namely Ctenodactylus gondii [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasmosis predominantly is asymptomatic in immunocompetent persons, while may cause severe complications with life-threatening outcomes in immunosuppressed persons such as human immunodeficiency virus/acquired immune deficiency syndrome subjects, patients with malignancy and transplant recipients [ 3 10 13 14 15 ]. Upon maternal infection, fetus is probably to be exposed with vertical transmission, which may cause abortion in those pregnant women that acquired toxoplasmosis during her pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation